106k views
4 votes
3(2x - 5)+ 5(x - 6)=-1

Solve for x

User Mtelesha
by
4.8k points

2 Answers

3 votes
X=4

How did I get this?
3(2x-5)+5(x-6)=-1
(6x-15)+(5x-30)
11x-45=-1
11x=44
x=4

I put it in parentheses so it’s easier to understand
First you’re going to distribute 3 to the 2x and -5 so 6x-15. Then you will do the same with the 5 so 5x-30. Combine like terms- 6x+5x and -15-30. Once you get 11x-45=-1 move the -45 over. Since it’s negative you’re going to add. 45+-1=44. After you have moved over the -45 you should have 11x=44. Lastly you are going to divide 44 by 11 which give you your answer x=4.
User Masroor
by
5.1k points
4 votes

Answer:

x= 4

Explanation:

User Charlweed
by
4.8k points